Clinical and Physiological Events That Contribute to the Success Rate of Finding "Optimal" Cerebral Perfusion Pressure in Severe Brain Trauma Patients. Issue 9 (September 2015) - Weersink, Corien S. A.; Aries, Marcel J. H.; Dias, Celeste; Liu, Mary X.; Kolias, Angelos G.; Donnelly, Joseph; Czosnyka, Marek; van Dijk, J. Marc C.; Regtien, Joost; Menon, David K.; Hutchinson, Peter J.; Smielewski, Peter
<x xml:space="preserve">Abstract</x> Objective: Recently, a concept of an individually targeted level of cerebral perfusion pressure that aims to restore impaired cerebral vasoreactivity has been advocated after traumatic brain injury. The relationship between cerebral perfusion pressure and pressure reactivity index normally is supposed to have a U-shape with its minimum interpreted as the value of "optimal" cerebral perfusion pressure. The aim of this study is to investigate the relation between the absence of the optimal cerebral perfusion pressure curve and physiological variables, clinical factors, and interventions. Design: Retrospective analysis of prospectively collected data. Setting: Neurocritical care units in two university centers. Patients: Between May 2012 and December 2013, a total of 48 traumatic brain injury patients were studied with real-time annotation of predefined clinical events. Interventions None. Measurements and Main Results: All patients had continuous monitoring of arterial blood pressure, intracranial pressure, and cerebral perfusion pressure, with real-time calculations of pressure reactivity index and optimal cerebral perfusion pressure using ICM+ software (Cambridge Enterprise, University of Cambridge, Cambridge, UK). Selected clinical events were inserted on a daily basis, including changes in physiological variables, sedativeanalgesic drugs, vasoactive drugs, and medical/surgical therapies for intracranial hypertension. The collected data were divided into 4-hour periods, with the primary outcome being absence of the optimal cerebral perfusion pressure curve. For every period, mean values (± SDs) of arterial blood pressure, intracranial pressure, pressure reactivity index, and other physiological variables were calculated; clinical events were organized using predefined scales. In 28% of all 1, 561 periods, an optimal cerebral perfusion pressure curve was absent. A generalized linear mixed model with binary logistic regression was fitted. Absence of slow arterial blood pressure waves (odds ratio, 2.7; p < 0.001), higher pressure reactivity index values (odds ratio, 2.9; p < 0.001), lower amount of sedative-analgesic drugs (odds ratio, 1.9; p = 0.03), higher vasoactive medication dose (odds ratio, 3.2; p = 0.02), no administration of maintenance neuromuscular blockers (odds ratio, 1.7; p < 0.01), and following decompressive craniectomy (odds ratio, 1.8; p < 0.01) were independently associated with optimal cerebral perfusion pressure curve absence. Conclusions: This study identified six factors that were independently associated with absence of optimal cerebral perfusion pressure curves.